Technology transfer in clean development mechanism (CDM) projects: lessons from China - Xie, Linna; Zeng, Saixing; Zou, Hailiang; Tam, Vivian W. Y.; Wu, Zhenhua (Technological and Economic Development of Economy, 2014)
China has become the largest host country of Clean Development Mechanism (CDM) in the world. This article provides an assessment of international technology transfer (TT) based on 500 registered Chinese CDM projects. It reveals that the projects hosted by large state-owned enterprises (SOEs), not Hydro and Wind projects, with foreign consultants or developers, commonly involve TT. Projects located in the comparatively developed regions such as Eastern China are more likely to involve TT. The findings indicate that the mitigation potential of non-SOEs, energy efficiency (EE) and other projects, has not been fully explored in China, which can be facilitated using advanced mitigation technologies.